دراسة فقهية حتليلية:(NFT) االستثمار يف الرموز غري قابلة لالستبدال = Non-Fungible Tokens (NFT) investment: a juristic and analytical study - Fadzil, Noor Fatini Izzati; Busari, Saheed Abdullahi (UM, 2024)
Non-fungible tokens (NFT) are considered unique digital assets recorded on the blockchain whose ownership and authenticity cannot be duplicated, exchanged, or divided but can be transferred by the owner, allowing the selling and trading of NFT through the blockchain. This study addresses the issues relating to the extent of NFT compliance with Islamic law. It sheds light on the concept of symbols that are not replaceable and presents the opinions of contemporary jurists in dealings with NFT based on a juristic adaptation of these transactions.The study is qualitatively based and using an inductive approach to collect library information and analytical approach to clarify the issue and present the opinions of the jurists. The study found that investing in non-fungible tokens is legally permissible, but the principles of Shariah must be adhered to when dealing with them because they are among the things that were not prevented except by legal evidence. NFTs should be items of legal value that benefit people, and are free from illegal activities such as usury, fraud, and gambling. The study recommends an urgent need for Shariah scholars and technology experts to create an NFT platform that is compatible with Islamic Shariah, and allowing Muslims to participate in it.